AKULTURASI PADA ARSITEKTUR MASJID SYEKH ZAINAL ABIDIN HARAHAP DI KOTA PADANG SIDEMPUAN - Fepri Dayanti Harahap; Riyan Kurniawan; Apriani Harahap (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
This research examines the Syekh Zainal Abidin Harahap Mosque as the oldest mosque in Padang Sidempuan City which was founded in 1880 which was self-educated by one of the religious leaders in Padang Sidempuan City, Syekh Zainal Abidin Harahap and still exists today. The study is seen from various sides, namely the development of mosques, acculturation of mosque architecture, and the role of the Sheikh Zainal Abidin Harahap mosque. This mosque has its own uniqueness from other mosques, namely the acculturation of culture found in the mosque, this is the reason why pilgrims visit this mosque for religious tours in addition to performing worship. The acculturation comes from Arabic, Javanese, and Hindu cultures. The Sheikh Zainal Abidin Harahap Mosque has been legalized as a Cultural Heritage object. This type of research is qualitative research using 4 stages of the historical method, namely, 1) Heuristics, 2) Source Criticism, 3) Interpretation, 4) Historiography. This research will be very useful for the field of education, especially the history of the entry of Islam into Indonesia and local history.